Gene expression profile during functional maturation of a central mammalian synapse - Körber, Christoph; Dondzillo, Anna; Eisenhardt, Gisela; Herrmannsdörfer, Frank; Wafzig, Oliver; Kuner, Thomas (European journal of neuroscience, 2014)
Calyx of Held giant presynaptic terminals in the auditory brainstem form glutamatergic axosomatic synapses that have advanced to one of the best-studied synaptic connections of the mammalian brain. As the auditory system matures and adjusts to high-fidelity synaptic transmission, the calyx undergoes extensive structural and functional changes - in mice, it is formed at about postnatal day 3 (P3), achieves immature function until hearing onset at about P10 and can be considered mature from P21 onwards. This setting provides a unique opportunity to examine the repertoire of genes driving synaptic structure and function during postnatal maturation. Here, we determined the gene expression profile of globular bushy cells (GBCs), neurons giving rise to the calyx of Held, at different maturational stages (P3, P8, P21). GBCs were retrogradely labelled by stereotaxic injection of fluorescent cholera toxin-B, and their mRNA content was collected by laser microdissection. Microarray profiling, successfully validated with real time quantitative polymerase chain reaction and nCounter approaches, revealed genes regulated during maturation. We found that mostly genes implicated in the general cell biology of the neuron were regulated, while most genes related to synaptic function were regulated around the onset of hearing. Among these, voltage-gated ion channels and calcium-binding proteins were strongly regulated, whereas most genes involved in the synaptic vesicle cycle were only moderately regulated. These results suggest that changes in the expression patterns of ion channels and calcium-binding proteins are a dominant factor in defining key synaptic properties during maturation of the calyx of Held.